Can we talk about price with patients when choosing antiretroviral therapy? A survey with people living with HIV and prescribers in France - Yazdan Yazdanpanah; Philippe Morlat; Marie Préau; Cécile Goujard; Nikos Kalampalikis; Gilles Peytavin; Elisabeth Bouvet; Emmanuelle Papot; Marjolaine Doumergue; Fabrice Pilorgé; Guillemette Quatremère; Philippe Arnaud; et al. (BMJ Open, 2021)
Objective The aim of this study was to evaluate people living with HIV (PLWH) and HIV specialist prescribers’ perception of discussing antiretroviral therapy (ART) price in PLWH’s care and the acceptability of choosing or switching to various types of less expensive ARTs.Design Cross-sectional surveys (one in a convenience sample of PLWH and one in a voluntary response sample of HIV specialist prescribers).Setting and participants The surveys were conducted among PLHW attending an HIV clinic in the North of Paris (cohort of 4922 PLWH in 2016), and HIV specialists working in French HIV clinics (210 across 12 districts/28), between January and June 2016.Method Self-administered questionnaires were constructed using data collected during focus groups with PLWH and prescribers. Pretests were carried out to select the questions and items. Descriptive analyses of the 129 complete questionnaires of PLWH and 79 of prescribers are presented.Results Among PLWH, 128/129 were on ART and 54% (69/128) gave a fair estimation of the price of their current regimen. Among prescribers, 24% (19/79) thought that their patients knew this price. Taking into account the price of ART was not perceived as a negative step in the history of French response to HIV epidemic for 53% (68/129) of PLWH and 82% (65/79) of prescribers. Seventy-seven PLWH (60%) would agree to switch to less expensive antiretroviral regimens (as effective and with similar adverse events) if pills were bigger; 42 (33%) if there were more daily doses, and 37 (29%) if there were more pills per dose; prescribers were more circumspect.Conclusion A high proportion of PLWH gave a fair estimate of their ART price and this seemed unexpected by HIV specialists. Consideration of drug prices when choosing ART was perceived as conceivable by PLWH and prescribers if effectiveness and tolerance were also considered.